Enhancing inertia in parallel VSGs: A power distribution strategy with washout filtering and adaptive virtual impedance - Kali Charan Pradhan; Kanungo Barada Mohanty (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
To address the reactive power-sharing problem employing sustaining inertia for a parallel microgrid with varying line impedances, this research suggests an innovative and forthright stability analysis of a virtual synchronous generator's (VSG) washout filter-based decentralized adaptive virtual impedance regulator employing a state space analysis technique. Typically, traditional VSGs mimic the behavior of synchronous generators without concentrating on eliminating undesired low-frequency dynamics, which under some circumstances may cause their reaction to be less optimized or slower. In order to improve the dynamic response of the VSG, this paper integrates washout filtering techniques. This improves high-frequency control, which is crucial for maintaining system stability, and enables the system to react to high-frequency shocks more successfully. This technique enhances the system's ability to provide more precise and prompt control during fleeting events, such as malfunctions or sudden changes in generation or demand. Enhancing the system's transient response without requiring more physical inertia is one of the most important breakthroughs of the washout filter-based VSG. The state space analysis method has been used to tune some parameters for the system's stability. An adaptive virtual impedance regulator is adopted to atone for the line impedance, which does not require any physical line impedance information to suppress the current flowing between VSGs and lower reactive power-sharing faults. The proposed washout filter-based VSG has an inherent stability characteristic of reconstructing and compensating for frequency and voltage fluctuation during transient with supporting inertia to the system. MATLAB/Simulink initially simulates this control approach, ensuring its functionality in a controlled environment. It is additionally confirmed on the hardware-in-loop OPAL-RT 4510 digital simulator, validating its performance and reliability.